Failure Mode and Effect Analysis for a Programmable Logic Controller-Based Control Unit for a Miniature Neutron Source Reactor Pneumatic Transfer System - H. K. Obeng; E. O. Amponsah-Abu; B. J. B. Nayrko; R. Edziah; P. D. Gasu; A.G. Ampong (Journal of Electrical and Computer Engineering)
The Pneumatic Transfer System (PTS) is an auxiliary system of Ghana Research Reactor-1 (GHARR-1) used to transfer the sample capsule in and out of the reactor irradiation sites. The PTS′ controller unit design and construction was carried out because the original transfer system was not designed to operate in Cyclic Neutron Activation Analysis (CNAA). To address these situations, a Programmable Logic Controller (PLC) has been used to design and construct a control unit to facilitate a CNAA application for GHARR-1. The design has been simulated successfully using LOGO! Soft Comfort software, version 8. A Failure Mode and Effect Analysis (FMEA) was conducted on the PTS Control Unit (PTSCU) to evaluate and document, by item failure mode analysis, the potential impact of each functional or hardware failure of the control unit, personnel and system safety, system performance, maintainability, and maintenance requirements. Each potential failure is ranked by the severity of its effect so that appropriate corrective actions can be taken to eliminate or control the high-risk items. The result obtained upon the analysis shows that the likelihood of occurrence of failures, detection, and severity on the control unit is low per the risk priority number. The paper outlines the severity classification and description used in FMEA, the likelihood of detecting various failures of components, and failure causes and effect.